Advances in Thermal Spray Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Thermal spray technology has been widely adopted industrially to combat diverse forms of surface degradation caused by wear, corrosion, oxidation, high thermal load, etc. Nonetheless, improvements in coating quality are incessantly sought to further enhance durability and/or performance of components operating in increasingly aggressive environments. This has led to technology advancements on various fronts, spanning feedstock materials, process variants, torch designs, coating architectures, etc. These have also been complemented by developments in closely allied areas to accommodate novel substrate materials, explore post-treatments, investigate coating behaviour under varied harsh conditions and harness benefits of artificial intelligence/neural networking. All of the above, along with efforts to improve diagnostic tools and create reliable control systems, have been driven by the desire to achieve robust shop-floor thermal spray capabilities to consolidate existing applications and spur new ones. This book is a compilation of twelve exciting contributions made for the Special Issue on “Advances in Thermal Spray Technology”, and showcases some of the above developments that are currently attracting interest in the field.